2018
DOI: 10.1103/physrevc.97.054622
|View full text |Cite
|
Sign up to set email alerts
|

Charge distributions of Ra recoil ions produced in C12+Pb fusion-evaporation reactions

Abstract: Charge state distributions of the Ra recoil ions produced in the 12 C + Pb fusion-evaporation reactions have been obtained by measuring their yields as a function of the high voltage applied to an electrostatic deflector. Well-defined two-humped yield curves for evaporation residues (ERs) were observed. Such observations can be explained by the different sets of charge states inherent in Ra recoil ions. These charge sets correspond to the equilibrated and nonequilibrated components, as earlier observed for eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…It is assumed that ERs knocked out from a target by heavy ion (HI) projectiles have a very broad charge state distribution. Besides the equilibrated 'solid' component [13][14][15], ERs have much higher charge states corresponding to the non-equilibrated component [16][17][18][19][20]. This component arises from the inner atomic shells ionization induced by the conversion of nuclear transitions in ERs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is assumed that ERs knocked out from a target by heavy ion (HI) projectiles have a very broad charge state distribution. Besides the equilibrated 'solid' component [13][14][15], ERs have much higher charge states corresponding to the non-equilibrated component [16][17][18][19][20]. This component arises from the inner atomic shells ionization induced by the conversion of nuclear transitions in ERs.…”
Section: Discussionmentioning
confidence: 99%
“…In further consideration, it was assumed that the reliable initial charge state distribution for ionized 252 No ERs escaping the 208 Pb target is the composition of the 'normal solid' component and of the non-equilibrated one. The 'normal solid' component corresponds to the equilibrated charge-state distribution for HIs passed through a solid [13][14][15], whereas the non-equilibrated component has charges which are much higher than 'normal' ones [16][17][18][19][20] (see Section I). The analysis of charge state distributions for ERs of different masses and velocities showed that the number of charge states for the non-equilibrated component N neq exceeds those for the equilibrated one N eq by a factor of 2-4.…”
Section: Monte Carlo Simulations Of Charge-changing Process For Ersmentioning
confidence: 99%
See 2 more Smart Citations
“…These reviews provide a crucial theoretical background in terms of the data collection to date. The CSDs are normally measured by the standard electromagnetic techniques [21][22][23][24] and in order to understand the measured equilibrium charge state data, many empirical formulas such as Thomas-Fermi model, Bohr model, Betz model, Nikolaev-Dmitriev model, To-Drouin model, Shima-Ishihara-Mikumo model, Itoh model, Ziegler-Biersack-Littmark model, Schiwietz model, etc., have been developed in tune with the experimental results from electromagnetic measurements [25 and references therein]. Interestingly, in some distinct cases, like, calculation of non-equilibrium charge state distribution [26,27], estimation of equilibrium target thickness [28], etc., the empirical predictions readily fail to estimate desired parameters.…”
Section: Introductionmentioning
confidence: 99%